A microstrip antenna design with multislots embedded into the ground plane for circular polarization. Issue 1 (29th March 2012) - Sim, C. Y. D.; Han, T. Y.; Yang, B. H.
Abstract A single probe‐fed square microstrip antenna with two pairs of asymmetric narrow slots loaded into the ground plane for circular polarization (CP) is studied. To allow a simple fine tuning CP mechanism, the method of loading an additional square slot into the center of the ground plane is introduced into this proposed antenna. By tuning the overall‐size of this center square slot, the CP frequency can be easily tuned with minor effects on the CP performances. Furthermore, good axial ratio (AR) value of around 0.5 is also measured at 1575 MHz, which is suitable for GPS operation. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.